Static and dynamic analysis of rectangular sandwich plates. - Mallakunta, Narendra. (University of Ottawa (Canada), 1990)
The static and dynamic characteristics of homogeneous rectangular plates and rectangular sandwich plates are studied by the finite element method using a 8-node isoparametric rectangular element. A computer code utilizing the finite element method is developed to generate solutions for the static and dynamic analysis of homogeneous plates and sandwich plates for conditions of plane stress, plane strain, bending, and combined stress and bending for small deformation problems only. However, in this work, the scope is limited to bending problems only. Further, only the values for the center deflection are generated, in the static analysis, even though the code has the capability to generate the various stress components. In the dynamic analysis, the natural frequency and the associated mode shapes are determined. The boundary conditions are taken as free, simply supported, clamped edge constraints and their combinations. Uniformly distributed loads, concentrated loads or a combination of both can be applied. This study concentrates on free vibration problems in the case of the dynamic analysis. The effect of considering non-uniform shear distribution in the core of the sandwich plate is studied for both the static and dynamic analysis. The impact of considering two different orders of numerical integration is also studied. (Abstract shortened by UMI.)
Keywords: Engineering, Mechanical.